Educational Intervention to Enhance Knowledge and Demonstrate Wound‑Care Skills in Managing Injuries Among Students at Cibitung Senior High School, Bekasi Regency - Melti Suriya; Rizky Fitri Andini; Farozi Farozi; Zuriati Zuriati; Hadi Permana; Gilang Khariansyah (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2026)
Minor injuries such as cuts, abrasions, and bruises frequently occur among students during school activities. Insufficient knowledge regarding proper wound care may increase the risk of infection and delay the healing process. This community service program aimed to improve students’ knowledge of basic wound care as first aid management for minor injuries through structured health education and demonstration sessions. The program was conducted on December 11, 2025, at SMAN 2 Cibitung and involved 40 students. The intervention consisted of interactive health education covering wound types, infection prevention, and step-by-step wound management procedures, followed by a practical demonstration using teaching aids. Students’ knowledge was assessed using a structured questionnaire administered before (pre-test) and immediately after (post-test) the intervention. A one-group pretest–posttest design was applied. Pre-test results indicated that 62.5% of students had poor knowledge, 32.5% had moderate knowledge, and 5.0% had good knowledge, with a mean score of 54.10 ± 12.30. After the intervention, no students remained in the poor category; 17.5% demonstrated moderate knowledge and 82.5% achieved good knowledge. The mean post-test score increased to 86.25 ± 9.40. The mean difference was 32.15 points (95% CI: 28.60–35.70), and paired sample t-test analysis showed a statistically significant difference between pre-test and post-test scores (p = 0.000). In conclusion, school-based health education combined with demonstration was associated with increased student knowledge of wound care as first aid for minor injuries. Further evaluation with follow-up assessment is recommended to examine long-term knowledge retention.